2004
DOI: 10.1161/01.cir.0000125853.51637.c8
|View full text |Cite
|
Sign up to set email alerts
|

Decision Guidelines for Prophylactic Replacement of Björk-Shiley Convexo-Concave Heart Valves

Abstract: Background-Because of risk of outlet strut fracture, prophylactic replacement should be considered for Björk-Shiley convexo-concave (BScc) valve recipients. We assessed the effects of epidemiological and decision-analytic guidelines on actual BScc valve replacement. Methods and Results-We performed a retrospective cohort study including all 2263 Dutch BScc patients with a mean follow-up of 11.3 years (range, 0 to 23 years). Outcomes were outlet strut fracture, mortality, and BScc valve replacement. For the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Prophylactic replacement of these valves which were prone to fracture was a concern especially in the early years of implantation of BSV and this peak of replacement was mainly due to infective endocarditis (9) . The other peaks of replacement were mainly after the identification and publication of risk factors for outlet strut fracture in 1992 (10) . However, there have been debates on the necessity of these replacements.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic replacement of these valves which were prone to fracture was a concern especially in the early years of implantation of BSV and this peak of replacement was mainly due to infective endocarditis (9) . The other peaks of replacement were mainly after the identification and publication of risk factors for outlet strut fracture in 1992 (10) . However, there have been debates on the necessity of these replacements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis of manufacturers data showed that several aspects of the manufacturing process (eg, repetitive testing) also increased the risk of outlet strut fractures . Based on these risk factors, advisory algorithms were devised to aid cardiothoracic surgeons in making a case‐to‐case decision on prophylactic BSCC replacement . It was concluded that each case should be assessed individually for a proper balance between surgical mortality and gain in life expectancy after reoperation, against the risk of OSF and subsequent loss of life expectancy.…”
Section: Indications For Prophylactic Reoperative Valve Replacement?mentioning
confidence: 99%
“…pening angle, valve size greater than or equal to 29 mm, mitral position) prophylactic valve replacement has been shown to increase the life expectancy [46]. The strut fracture usually results in the abrupt onset of dyspnea, loss of consciousness, or cardiovascular collapse due to embolization of the disk and acute severe valvular regurgitation.…”
Section: Evaluation Of Structural Prosthesis Deteriorationmentioning
confidence: 99%